Automatic Transmission Clutch Engagement Control based on Improved NSGA-Ⅱ Algorithm - Yun Yu; Cuie Tang (Jixie chuandong)
To improve the stability of the vehicle in the starting process and prolong the service life of the clutch， a dynamics model of the engagement process is established according to the motion state of the active and driven discs of the clutch. The NSGA-Ⅱ algorithm is introduced to solve the multi-objective optimization problem， and the crossover operator of normal distribution and adaptive mutation operator are adopted to improve it，which keeps the diversity of population and effectively prevents falling into local optimum. Finally，the engagement speed and time of clutch are taken as the design variable，and the impact degree and sliding friction work are taken as the optimization objective function， and the simulation experiment is carried out. The simulation results show that the improved NSGA-Ⅱ algorithm has better Pareto front and faster convergence speed， and distribution is more uniform， obviously superior to the other two comparison algorithms， and the smaller impact degree and sliding friction work can be obtained by smoothly controlling the engagement speed of clutch in the condition of the same joint time，which provides technical support for the design of clutch engagement control strategy.